Book Review: A “indústria” dos fundos financeiros. Potência, estratégias e mobilidade no capitalismo contemporâneo [The “industry” of financial funds. Power, strategies and mobility in contemporary capitalism], by Roberto Moraes Pessanha - Zanotelli, Claudio (Geografares, 2019)
Book Review:  A “indústria” dos fundos financeiros. Potência, estratégias e mobilidade no capitalismo contemporâneo [The “industry” of financial funds. Power, strategies and mobility in contemporary capitalism], by Roberto Moraes Pessanha.The author presents in the book, as indicated in the preface by Sandra Lencioni “(...) an analysis of the frenetic mobility of financial funds in contemporary capitalism in which finance develops a world of fiction in which value is confused with anti-value, and capital, with fictitious capital. Central to the text, the discussion of financial funds constitutes the motivation chosen to alert us about the risks of barbarism that surrounds us in this phase of capitalist development that can compromise the entire civilizational process that we have experienced so far”. A book, therefore, fundamental for us to understand the current moment of capitalism in its period of acute financialization and its impacts on societies and their spaces.
Keywords: Book Review: A “indústria” dos fundos financeiros. Potência, estratégias e mobilidade no capitalismo contemporâneo [The “industry” of financial funds. Power, strategies and mobility in contemporary capitalism], by Roberto Moraes Pessanha